Ocean acidification at a coastal CO2 vent induces expression of stress-related transcripts and transposable elements in the sea anemone Anemonia viridis - Urbarova, Ilona; Forêt, Sylvain; Dahl, Mikael; Emblem, Åse; Milazzo, Marco; Hall-Spencer, Jason M.; Johansen, Steinar D. (PLOS ONE, 2019)
Ocean acidification threatens to disrupt interactions between organisms throughout marine ecosystems. The diversity of reef-building organisms decreases as seawater CO2 increases along natural gradients, yet soft-bodied animals, such as sea anemones, are often resilient. We sequenced the polyA-enriched transcriptome of adult sea anemone Anemonia viridis and its dinoflagellate symbiont sampled along a natural CO2 gradient in Italy to assess stress levels in these organisms. We found that about 3.1% of the anemone transcripts, but <1% of the Symbiodinium sp. transcripts were differentially expressed. Processes enriched at high seawater CO2 were linked to cellular stress and inflammation, including significant up-regulation of protective cellular functions and down-regulation of metabolic pathways. Transposable elements were differentially expressed at high seawater CO2, with an extreme up-regulation (> 100-fold) of the BEL-family of long terminal repeat retrotransposons. Seawater acidified by CO2 generated a significant stress reaction in A. viridis, but no bleaching was observed and Symbiodinium sp. appeared to be less affected. These observed changes indicate the mechanisms by which A. viridis acclimate to survive chronic exposure to ocean acidification conditions. We conclude that many organisms that are common in acidified conditions may nevertheless incur costs due to hypercapnia and/or lowered carbonate saturation states.